Implementasi CSR Asia Pulp & Paper Sinar Mas Melalui Program Desa Makmur Peduli Api - siti qonaah qonaah (Jurnal Komunikasi, 2020)
AbstrakThe purpose of this study was to determine the Implementation of Asia Pulp & Paper Corporate Social Responsibility Sinar Mas through Desa Makmur Pemadam Api program. The efforts carried out by Pulp & Paper Asia Sinar Mas in community empowerment in the village of Dataran Kempas Jambi Village to increase the productivity of ginger and the village of West Kalimantan bahta to increase the productivity of Honey. Ginger and honey are food ingredients that can maintain stamina during the pandemic coronavirus epidemic. In this study, researchers used a qualitative approach and case studies. As a research method that illustrates that Sinar Mas's Asia Pulp & Paper Corporate Social Responsibility through the program, Desa Makmur Pemadam Api with community empowerment has been able to increase the productivity of ginger and honey so that the needs for ginger and honey can be met and public health can be maintained the welfare of the people living in around this forest can increaseKeywords: Keywords: Corporate Social Responsibility, Community Empowerment.